2005
DOI: 10.14712/18059694.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Urinary Excretion in Diabetic Adolescents

Abstract: Objective: to define peculiarities of urinary magnesium (Mg) excretion in diabetic adolecents; to elucidate gender-related differences in Mg urinary excretion; to determine urinary Mg excretion differences between diabetic and age-matched healthy children. The diurnal, nocturnal and 24–h urinary Mg level in adolescent boys and girls (aged 13–17 years) with type I diabetes mellitus (DM) and in age-matched control groups of healthy boys and girls was examined. Additionally the adolescent girls were examined duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…44 Actually, McNair et al reported the occurrence of a definite hypermagnesuria in 55% of 215 outpatients with IDDM. 18 Increased magnesium urinary excretion with a male predominance has also been reported in children and adolescents with T1DM compared with their healthy peers, 8,34,45,46 as well as in adult patients with diabetes; 26,27,29,35 however, inconsistent findings have also been published. 28 As far as the relationship between magnesium status and glycemic control is concerned, incompatible results exist on this topic in youth with T1DM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…44 Actually, McNair et al reported the occurrence of a definite hypermagnesuria in 55% of 215 outpatients with IDDM. 18 Increased magnesium urinary excretion with a male predominance has also been reported in children and adolescents with T1DM compared with their healthy peers, 8,34,45,46 as well as in adult patients with diabetes; 26,27,29,35 however, inconsistent findings have also been published. 28 As far as the relationship between magnesium status and glycemic control is concerned, incompatible results exist on this topic in youth with T1DM.…”
Section: Discussionmentioning
confidence: 98%
“…reported the occurrence of a definite hypermagnesuria in 55% of 215 outpatients with IDDM . Increased magnesium urinary excretion with a male predominance has also been reported in children and adolescents with T1DM compared with their healthy peers, as well as in adult patients with diabetes; however, inconsistent findings have also been published …”
Section: Discussionmentioning
confidence: 98%
“…A possible mechanism explaining the lower urine potassium concentration in CON versus MOD during exercise and recovery could be increased activation of the renal outer medullary potassium channels in MOD due to lower magnesium concentration (as observed in the serum magnesium results) [28,29]. Lower plasma magnesium concentration has been reported in PWT1D compared to people without diabetes [30,31], which may be attributed to higher levels of urinary excretion of magnesium in those with T1D compared to non-diabetic controls [32].…”
Section: Discussionmentioning
confidence: 90%
“…In the Atherosclerosis Risk in Community Study, hypomagnesemia doubled the odds for T2DM (10). Patients with T2DM have a 30% higher frequency of hypomagnesemia compared to the general public and increased urinary Mg 2+ losses (7, 17, 18). However, the etiology of urinary Mg 2+ losses in diabetes mellitus is unclear and may include poor Mg 2+ intake, glomerular hyperfiltration, osmotic diuresis, and metabolic acidosis (19).…”
Section: Introductionmentioning
confidence: 99%